2020
DOI: 10.1074/jbc.ra119.011280
|View full text |Cite|
|
Sign up to set email alerts
|

The E3 ubiquitin ligase STUB1 attenuates cell senescence by promoting the ubiquitination and degradation of the core circadian regulator BMAL1

Abstract: Cell senescence is one of the most important processes determining cell fate and is involved in many pathophysiological conditions, including cancer, neurodegenerative diseases, and other aging-associated diseases. It has recently been discovered that the E3 ubiquitin ligase STIP1 homology and U-box–containing protein 1 (STUB1 or CHIP) is up-regulated during the senescence of human fibroblasts and modulates cell senescence. However, the molecular mechanism underlying STUB1-controlled senescence is not clear. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…57 ), exemplified by the ubiquitin-dependent spatiotemporal regulation of CRY proteins, the major negative clock regulators 58 . Several studies have provided insights into ubiquitin-dependent events modulating core clock proteins and their effects [59][60][61] . Given the unexpected degree of phosphorylation-mediated signaling temporally regulated in vivo 52 , we wondered if ubiquitination shows similar oscillations.…”
Section: Resultsmentioning
confidence: 99%
“…57 ), exemplified by the ubiquitin-dependent spatiotemporal regulation of CRY proteins, the major negative clock regulators 58 . Several studies have provided insights into ubiquitin-dependent events modulating core clock proteins and their effects [59][60][61] . Given the unexpected degree of phosphorylation-mediated signaling temporally regulated in vivo 52 , we wondered if ubiquitination shows similar oscillations.…”
Section: Resultsmentioning
confidence: 99%
“…The proteasome pathway was enriched in the high-risk group. Recent studies have also confirmed that some ubiquitin ligases participate in the degradation of core circadian clock genes through the ubiquitin-proteasome pathway, thereby controlling the biological functions of cells, including cell senescence ( Chen et al, 2018 ; Ullah et al, 2020 ). This cross-talk between circadian clock genes and the ubiquitin-proteasome pathway may be related to the prognosis of LUAD.…”
Section: Discussionmentioning
confidence: 96%
“…Ubiquitination plays a pivotal role in the core clock machinery (reviewed in 54 ), exemplified by the ubiquitin-dependent spatiotemporal regulation of CRY proteins, the major negative clock regulators 55 . Focused studies have provided insights into several ubiquitin-dependent events modulating core clock proteins and their effects 5658 . Given the unexpected degree of phosphorylation-mediated signaling temporally regulated in vivo 51 , we wondered if ubiquitination shows similar oscillations.…”
Section: Resultsmentioning
confidence: 99%